(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The past 20th century has witnessed a renewed interest in the approaches of Aristotelian philosophy, especially from the hand of the German philosopher Martin Heidegger. Well, along with this return to the study of peripatetic philosophy, a new interest in the philosophy of being of Thomas Aquinas has emerged as a parallel, particularly in his notion of esse ut actus essendi. This has led to various lines of research, sometimes confronted, which have dealt mainly with the question of the Tomasian reception of the notion of being and the aspects involved in it. In this work we will try to make known some important aspects of this reception, as well as of those different lines of interpretation confronted.